Outcomes following resective and disconnective strategies in the treatment of epileptic spasms: a systematic review of the literature and individual patient data meta-analysis - Cottier, Rachel; Niazi, Farbod; Goël, Keshav; Korman, Catherine; Porte, Tiphaine; Ducruet, Thierry; Cossu, Giulia; Briscoe, Christina; Singh, Avantika; Harini, Chellamani; Ibrahim, George M.; Fallah, Aria; et al. (Frontiers in Neurology, 2024)
Epileptic spasms (ES) are a unique seizure type typically presenting in the form of infantile epileptic spasms syndrome (IESS) with characteristic hypsarrhythmia on scalp EEG and a preponderance with developmental delay or regression. While pharmacotherapy is the mainstay of treatment, surgical options, including disconnective or resective procedures, are increasingly recognized as viable therapeutic options for recurrent or persistent ES. However, limited data on safety, effectiveness, and prognostic factors hinder informed decision-making regarding surgery indications, timing, and intervention type. We performed a systematic review and an individual patient data meta-analysis (IPDMA) in accordance with PRISMA guidelines, focusing on surgical interventions for ES and reporting seizure outcomes using the Engel or ILAE scales. Twenty-six studies encompassing 358 ES patients undergoing resection/callosotomy were included. Participants undergoing other approaches (e.g., multiple subpial transections) or multimodality approaches were excluded from analysis. The median age at spasm onset was 6 months (IQR = 3.0–15.6), with a median age at surgery of 37 months (IQR = 17.2–76.8). Most patients (74.1%) exhibited additional seizure types. A total of 136 patients (35.8%) underwent corpus callosotomy (CC), of whom 125 (91.9%) had a complete callosotomy, while 11 (8.1%) had a partial callosotomy. Resective surgery was performed on 222 patients (58.4%). Among those who underwent resection, 109 (49.1%) had both lesional MRI findings and lateralized EEG abnormalities. Overall, 201 patients (56.1%) remained spasm-free at a median postoperative follow-up of 36 months (interquartile range, IQR = 21–60), including 52 (38.2%) from the callosotomy group and 149 (67.1%) from the resective surgery group. In the resective surgery cohort, patients with MRI-confirmed lesions (p = 0.026; HR = 0.53, 95% CI = 0.31–0.93) and those who underwent hemispherectomy (p = 0.026, HR = 0.46, 95% CI = 0.23–0.91) had better seizure outcomes. Only a minority (24.4%) underwent invasive EEG monitoring prior to ES surgery. Surgical treatment of ES proves effective, with two thirds of patients undergoing resective surgery and a third undergoing CC becoming spasm free. Post-operative developmental improvement was observed in 44 participants (65.7% of those with available data). The presence of lesional MRI and more extensive resection/disconnection (e.g., hemispherectomy) emerged as significant prognostic factors for spasm freedom and can inform clinical decision-making.